Design, Synthesis and Conformational Studies of Cyclic Tetrapeptides having βγ Fused Turns as HDAC Inhibitors. Issue 31 (17th August 2021) - Ghosh, Uttam; Basu, Moumita; Pal, Sudip; Meena, Sanjeev; Datta, Dipak; Ampapathi, Ravi Sankar; Kundu, Tapas K; Singh, Gajendra; Chakraborty, Tushar Kanti
Abstract: Histone deacetylases (HDACs) belong to a class of major targets for the development of anticancer drugs for which cyclic peptide‐based molecules are attracting wide attention. Here we show the synthesis, conformational and in silico analysis of tetrahydrofuran amino acid (TAA) based 15‐membered cyclic tetrapeptides (CTPs) containing hydroxamic acid side chain as potential HDAC inhibitors. NMR based solution studies in protected and deprotected forms reveal that the macrocycles are stabilized by 10‐membered β ‐turn as well as a 7‐membered γ ‐turn. This type of fused structures within the same macrocycle is not frequently sighted. Our initial in silico docking results indicated that the hydroxamic acid protected CTPs show promising binding with the class‐1 HDACs. We also noticed that the C‐chain with hydroxamic functional group attached on the ornithine sidechain did not affect the core structure of the peptide ring. Moreover, some of these cyclic tetrapeptides with hydroxamic acid side chain exhibited an induction of acetylation of histones on preliminary cell‐based experiments. Our initial results provide an insight into the development of HDAC inhibitors based on the CTPs with novel βγ fused turns which have not been explored yet. Abstract : Tetrahydrofuran amino acid (TAA) based 15‐membered cyclic tetrapeptides (CTPs) containing hydroxamic acid side chain with βγ fused turn structures showed very promising binding in silico with the class‐1 HDACs and differential HDAC inhibitory activities in preliminary cell‐based assays.